LASER-INDUCED SURFACE ACOUSTIC WAVES FOR THIN FILM CHARACTERIZATION - Radim Kudělka; Lukáš Václavek; Jan Tomáštík; Sabina Malecová; Radim Čtvrtlík (Acta Polytechnica CTU Proceedings, 2020)
Knowledge of mechanical properties of thin films is essential for most of their applications. However, their determination can be problematic for very thin films. LAW (Laser-induced acoustic waves) is a combined acousto-optic method capable of measuring films with thickness from few nanometers. It utilizes ultrasound surface waves which are excited via short laser pulses and detected by a PVDF foil. Properties such as Young’s modulus, Poisson’s ratio and density of both the film and the substrate as well as film thickness can be explored.Results from the LAW method are successfully compared with nanoindentation for Young’s modulus evaluation and with optical method for film thickness evaluation and also with literature data. Application of LAW for anisotropy mapping of materials with cubic crystallographic lattice is also demonstrated.